Каникулы в Простофилино - Донцова Дарья Аркадьевна (Иронический детектив, 2007)
Экземпляры: (20141203) / Инвентарный номер: 32070 / Цена: 102.00 / Сис.шифр: Р2 / Авт.знак: Д 67 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6